ANALISIS USABILITY APLIKASI VISIT PEMALANG MENGGUNAKAN METODE HEART METRICS - Ahmad Rozikin; Asnawi, Muhamad Fuat (CV Nature Creative Innovation, 2024)
This research aims to provide valuable insights for researchers and developers of the Visit Pemalang application, focusing on enhancing usability and user experience quality. To achieve this goal, several improvements are suggested, such as presenting appealing content and increasing user satisfaction to make the Visit Pemalang app more effective in meeting visitor needs and enhancing tourism experiences in Kabupaten Pemalang. The HEART Metrics method is utilized to measure user experience quality in the application, encompassing dimensions like Happiness, Engagement, Adoption, Retention, and Task Success. Data is collected through user observation and questionnaires tailored to the HEART Metrics dimensions. The analysis results indicate excellent performance in various HEART Metrics dimensions, particularly in Task Success, Engagement, and Happiness. Users can effectively complete tasks and feel content with their application experience. By implementing the findings from this study, developers can improve the usability and user experience quality of the Visit Pemalang application, elevate user satisfaction, and provide a superior tourism experience in Kabupaten Pemalang..